Teachers' Efforts to Improve Thematic Learning Outcomes Using a Tpack-Based Scientific Approach - Wandi, Afri; Marlia, Ade; Isnaniah, Isnaniah (CV. Strata Persada Academia, 2024)
This research aims to address the issue of low learning outcomes among third-grade students at SDN 08 Batang Lolo, which were below the Minimum Completeness Criteria (KKM). Observations revealed that the existing teaching methods, focused primarily on lectures and textbook usage, led to student disengagement and lack of motivation. To enhance student engagement and learning effectiveness, a TPACK-based scientific approach was proposed. This method integrates Technological Pedagogical Content Knowledge (TPACK), which encompasses technological, pedagogical, and content knowledge, facilitating a more dynamic and interactive learning environment. The study employed Classroom Action Research (PTK) during the 2023/2024 academic year, conducted over two cycles. Each cycle involved planning, action, observation, and reflection stages to improve teaching methods and evaluate their impact. The results demonstrated a significant improvement in student learning outcomes. In Indonesian language content, student achievement increased from 53% in cycle I to 87% in cycle II, while in PPKn content, it rose from 73% to 100%. The findings suggest that a TPACK-based scientific approach not only improves academic performance but also encourages student activity and creativity. Recommendations include the adoption of multimedia tools like PowerPoint to enhance teaching and learning processes. This study serves as a valuable reference for educators aiming to integrate technology into their pedagogical practices, ultimately contributing to higher quality education.